2018
DOI: 10.15406/jaccoa.2018.10.00390
|View full text |Cite
|
Sign up to set email alerts
|

Audit on documentation completeness after regional nerve blocks at University of Gondar referral hospital, 2018

Abstract: Practices of regional nerve block here in Gondar University Referral Hospital are expanding with multiple techniques and different approaches with increasing availability of equipments and medications. The demands of documentation of regional nerve block are growing well ,however there are no specified protocols which should be recorded for each individual nerve block, no separate record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…35 Another study conducted at the University of Gondar by Chekol W et al, 2018 found as all anesthetists did not wash their hands and wear sterile gowns throughout the procedure which is inline with our study. 36 In conflicting with our finding's various literature and clinical practice guidelines reported and recommended that while performing this spinal nerve block, it is vital to completely practice the standards of spinal anesthesia to ensure patient safety and enhance the better outcome. 23,24,37…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…35 Another study conducted at the University of Gondar by Chekol W et al, 2018 found as all anesthetists did not wash their hands and wear sterile gowns throughout the procedure which is inline with our study. 36 In conflicting with our finding's various literature and clinical practice guidelines reported and recommended that while performing this spinal nerve block, it is vital to completely practice the standards of spinal anesthesia to ensure patient safety and enhance the better outcome. 23,24,37…”
Section: Discussionmentioning
confidence: 81%
“…Another study conducted at the University of Gondar by Chekol W et al, 2018 found as all anesthetists did not wash their hands and wear sterile gowns throughout the procedure which is inline with our study. 36 …”
Section: Discussionmentioning
confidence: 99%
“…However if there is lack of adequate perioperative documentation, it will hinder the quality and safety of patient management, lead to legal implications and difficulty in getting briefed information during handover period. 4,5,15,16 Also adequate documentation of perioperative anaesthetic events will be valuable to subsequent anaesthetists who required to provide anaesthetic services to a patient for the future. 15,17,18 Conclusions This audit identified that there were significant improvements of post intervention documentation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Documenting and keeping readily accessible records are responsibilities of anaesthesia practitioners and anaesthetists. [4][5][6] The anaesthetic record has become a key element of good anaesthetic practices, which is helpful for other staff who will be involved in the management of the patients. It will safeguard against medico legal issues, facilitate effective monitoring of patients and is an important tool for research and audit and quality improvement in anaesthesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation